STUDY ON ULTRASONIC VIBRATION MILLING FORCE OF OPTICAL GLASS MATERIAL - ZHAO Jie; FU ZongXia (Jixie qiangdu)
In view of the problems such as low efficiency and surface cracks in optical glass processing,the experiment studied the influence of cutting parameters and acoustic parameters on milling forces and established a milling force model of optical glass ultrasonic vibration that based on the high frequency impact effect of ultrasonic vibration,through which on ultrasonic vibration milling of optical glass.The effects of factors such as milling speed,feed per tooth and milling depth on milling force were discussed through comparative experiments on ultrasonic vibration milling and conventional milling of optical glass.The experimental results show that under ultrasonic milling,the milling force is significantly lower than the conventional milling force.